Alienation In Adolescents: The Role Of Self Determination - Rahmawati Rahmawati; Widi Astuti (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Abstract: Purpose: This study aims to see the relationship between self determination and alienation in adolescents Subject and methods: e : This study uses a quantitative research design with the type of correlation. The number of research samples as many as three hundred and seventy six students obtained based on simple random sampling method that has certain criteria. Data was collected using an alienation scale and a self-determination scale. Result: The results showed that there was a negative correlation between self determination and alienation in adolescents which reached 42.2%. When viewed based on the aspect correlation between aspects of the alienation variable and self determination, the highest aspect is the aspect of normlesness, while the lowest is the aspect of powerlessness. The correlation between the aspects of the self determination variable and alienation shows that the relatedness aspect has the highest correlation, while the lowest is the competence aspect. Conclusion: There is a correlation between self determination and alienation in adolescents. Alienation is influenced by intrinsic motivation, namely self determination.